Training load issues in young handball players - Asker, M.; Møller, M. (Handball Sports Medicine, 2018)
As in many youth sports, handball provides kids and adolescents with the opportunity to develop physical fitness including coordination, speed, endurance, agility, power and strength as well as develop social skills. Indisputable, participating in sports activities from a young age has numerous health and social benefits. However, this development of physical fitness requires that the player can adapt to the applied training load. Otherwise, there is an increased risk of injuries or non-functional overreaching. Further, there is also a chance that the player will lack the motivation to continue with handball, due to either too much pressure or persistent or recurrent injuries. In this chapter, we will outline potential risk scenarios of overload specifically in the young handball player aged 12-19 and how to address these risk scenarios.